2018
DOI: 10.15244/pjoes/77072
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Developments and Biodiversity in Carabid and Staphylinid (Coleoptera: Carabidae and Staphylinidae) Fauna during the Application of Organic Fertilizers under Agroecosystem Conditions

Abstract: The aim of this work was to ascertain the influence of applying various doses of organic fertilizers on the occurrence of the Carabidae and Staphylinidae families. The research was carried out in five treatments: 1) control treatment, 2) 25 t ha-1 of farmyard manure, 3) 50 t ha-1 of bio-sludge, 4) 50 t ha-1 of farmyard manure, and 5) 100 t ha-1 of bio-sludge. Coleoptera was represented by 87,324 individuals, Carabidae with a dominance of 80.53 to 86.28%, and Staphylinidae from 5.36 to 8.32%. Carabidae recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The multivariate analysis of our results, of single soil arthropods in relation to land use showed that the predominance of taxa is linked to grass mixture, Pisum sativum, Triticum aestivum, T. spelta. The predominance of soil arthropods in the same crops is noted in (Porhajašová et al, 2018). We also noted the predominance of soil arthropods with phosphorus, nitrogen and potassium binding.…”
Section: Discussionsupporting
confidence: 63%
“…The multivariate analysis of our results, of single soil arthropods in relation to land use showed that the predominance of taxa is linked to grass mixture, Pisum sativum, Triticum aestivum, T. spelta. The predominance of soil arthropods in the same crops is noted in (Porhajašová et al, 2018). We also noted the predominance of soil arthropods with phosphorus, nitrogen and potassium binding.…”
Section: Discussionsupporting
confidence: 63%
“…Also, for collembolans, toxicity increases with the quantity of pig manure, whereby doses of 50, 75 and 100 t ha − 1 caused 100% mortality (Maccari et al, 2020). However, Porhajašová et al (2018) found 25 or 50 t ha − 1 to not impact the presence of beetles (Coleoptera). The applications of 600 kg N ha − 1 of pig manure led to a higher abundance of nematodes, compared to 150 kg N ha − 1 , possibly due to an increase in microbial biomass (Jiang et al, 2013).…”
Section: Management Ii: Spreading Phasementioning
confidence: 94%
“…The species richness of agroecosystems almost always exceeds the species richness of natural, resp. semi-natural landscape ( Ivanič Porhajašová et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%